2022
DOI: 10.3389/fmicb.2022.804429
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community, Fermentation Quality, and in vitro Degradability of Ensiling Caragana With Lactic Acid Bacteria and Rice Bran

Abstract: This study aimed to assess the effects of microbial inoculants and growth stage on fermentation quality, microbial community, and in vitro degradability of Caragana silage from different varieties. Caragana intermedia (CI) and Caragana korshinskii (CK) harvested at the budding (BU) and blooming (BL) stages were used as raw materials to prepare silage, respectively. The silages at each growth stage were treated for ensiling alone (control), with 5% rice bran (RB), a combination of RB with commercial Lactobacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…It has been suggested that altitude, plant composition and climate can influence the distribution of LAB ( Leong et al., 2014 ). After fermentation process, the portions of Pantoea and Rosenbergiella decreased significantly and were replaced by Lentilactobacillus , Levilactobacillus , Lactiplantibacillus , and Limosilactobacillus in different LAB inoculant treatments, which is in agreement with the results of You et al. (2022) .…”
Section: Discussionsupporting
confidence: 88%
“…It has been suggested that altitude, plant composition and climate can influence the distribution of LAB ( Leong et al., 2014 ). After fermentation process, the portions of Pantoea and Rosenbergiella decreased significantly and were replaced by Lentilactobacillus , Levilactobacillus , Lactiplantibacillus , and Limosilactobacillus in different LAB inoculant treatments, which is in agreement with the results of You et al. (2022) .…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have con rmed that paper mulberry is di cult to be well ensiled due to its low WSC, high moisture content [26]. Additives, such as LAB and bran, are often widely utilized to effectively improve the silage fermentation quality [27][28][29][30]. In this study, we found that silages treated with WB and LP + WB increased (P < 0.05) the CP, WSC and LA content and decreased (P < 0.05) pH compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread application of inoculants, the addition of Lactobacillus and fungi has become common practice to improve silage quality [17,22]. A prior study has demonstrated that rice bran contains soluble sugars, providing an adequate substrate for fermentation, thereby promoting the success of the fermentation process [23].…”
Section: Introductionmentioning
confidence: 99%